The Dilemma of Adopting Innovation in Media : Study Case of Data Journalism Practice in KOMPAS - Kusumawati, Utami Diah (LPPM Stikosa - AWS, 2023)
Using Everett M. Rogers’ diffusion of innovations theory, this paper analyzes how an innovation, such as data journalism, which comes out as a result of digital disruption is being adopted in the newsroom of a national media in Indonesia, KOMPAS. The presence of digital disruption which leads to the mushrooming of contents provided by non-journalists creates challenges for journalists. Data journalism with its core of accuracy and fact-based information comes as a solution for providing quality and solutions based journalism as believed by KOMPAS. The case study of KOMPAS involves interviewing its six media practitioners to find out elements of diffusion innovation theory, such as the characteristics of innovation, decisions-making process, and category of adopter, applied at KOMPAS to examine the factors behind the process of adoption of data journalism in its newsroom. This research shows that the adoption of innovation (data journalism) in a mainstream media like KOMPAS is heavily influenced by the decision to adopt the innovation by a powerful individual such as editor-in-chief, the alignment of the innovation with the company’s value and needs, the familiarity of its employee with the new method of journalism and a measured output.